(untitled) (Communications in Mathematical Research, 2019)
This paper considers the thermoelastic beam system of type III with friction dissipations acting on the whole system. By using the methods developed by Chueshov and Lasiecka, we get the quasi-stability property of the system and obtain the existence of a global attractor with finite fractal dimension. Result on exponential attractors of the system is also proved.